A heat-retaining fabric based on a heat-accumulating gold film and a preparation method thereof
Patent Information
- Application Number
- CN202410354913.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-27
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2044-03-27
AI Technical Summary
另外,面料的涂层和处理也可以提高面料的保温性,但涂层处理会使得面料的透气透湿性降低,面料穿着舒适性会随之降低,如何保证面料保温性能的同时使其具备较好的穿着性是保温面料研发有待解决的问题,本发明为此提出了一种基于蓄热金膜的保温面料及其制备方法
[0019]本发明的面料是在基布的基础上复合蓄热金膜获得的,蓄热金膜是先将纳米金分散于聚氨酯溶液中获得纺丝液,再将纺丝液经静电纺丝复合于基布上而形成的。在纳米金制备时,首先,通过积雪草酸与柠檬酸钠配合使用使制得的纳米金粒径更加均一且分散,面料具有优异的透气透湿及保温效果,使面料穿着舒适感得到提升;其次,通过添加腐殖酸钠,使面料抗菌性提升,且纳米金与腐殖酸钠混合后在振动的工况下进行摩擦处理,纳米金与腐殖酸钠之间的结合力强,纳米金不易产生团聚,保证面料具有持久的保温及抗菌效果。
Smart Images

Figure BDA0004760980660000051 
Figure BDA0004760980660000061 
Figure BDA0004760980660000091
Abstract
Description
Technical Field
[0001] This invention belongs to the field of clothing fabric technology, specifically relating to a heat-insulating fabric based on a heat-retaining gold film and its preparation method. Background Technology
[0002] The insulation performance of winter clothing is the most basic indicator for evaluating its quality. Fabrics with good insulation performance can maintain body temperature in cold environments, preventing discomfort and illness caused by hypothermia. Fabrics with poor insulation performance cannot effectively keep warm, making the body more susceptible to cold.
[0003] Currently, improving the thermal insulation performance of fabrics typically involves using highly insulating fiber materials and special weaving techniques. Additionally, coatings and treatments can also enhance the thermal insulation of fabrics, but coatings reduce breathability and moisture permeability, consequently decreasing wearing comfort. How to ensure both thermal insulation performance and good wearability is a problem that needs to be solved in the research and development of thermal insulation fabrics. This invention proposes a thermal insulation fabric based on a heat-retaining gold film and its preparation method. Summary of the Invention
[0004] The purpose of this invention is to provide a heat-insulating fabric based on a heat-retaining gold film and its preparation method in order to solve the above-mentioned problems.
[0005] The present invention achieves the above objectives through the following technical solutions:
[0006] As a first aspect of the present invention, the present invention provides a heat-insulating fabric based on a heat-storing gold film, the structure of which includes a base fabric and a heat-storing gold film laminated on the base fabric; wherein, the base fabric is woven from 100% nylon fiber as warp yarn and 60-80% viscose fiber composite with 20-40% corn fiber hollow yarn as weft yarn by weight percentage; the heat-storing gold film is formed by first dispersing nano-gold in a polyurethane solution to obtain a spinning solution, and then laminating the spinning solution onto the base fabric by electrospinning.
[0007] As a further optimization of the present invention, the warp yarn weaving density is 90-100 yarns / cm, the weft yarn weaving density is 70-80 yarns / cm, and the weaving structure is plain weave.
[0008] As a further optimization of the present invention, the corn fiber hollow yarn can be obtained by coating corn fiber with water-soluble fiber and then removing the water-soluble fiber through hydrolysis treatment. The water-soluble fiber is water-soluble polyvinyl alcohol fiber.
[0009] As a second aspect of the present invention, the present invention also provides a method for preparing a heat-insulating fabric based on a heat-retaining gold film as described in any of the above-mentioned embodiments, comprising the following steps:
[0010] (1) Preparation of base fabric: The base fabric is obtained by weaving nylon fiber as warp yarn and viscose fiber composite corn fiber hollow yarn as weft yarn using a fabric weaving machine;
[0011] (2) After filtering the aqueous solution of chloroauric acid through a 0.5 μm filter membrane, it is mixed with sodium citrate and asiatic acid, heated to boiling, and kept for 1-5 h to obtain a colloidal gold solution. Then, the colloidal gold solution is washed with ethanol and deionized water, centrifuged, and dried to obtain nano gold. The nano gold is mixed with sodium humate and rubbed at a speed of 80-100 r / min for 30-60 min under vibration.
[0012] (3) Disperse the nano gold obtained in step (2) in a polyurethane solution to obtain a spinning solution, and spin the spinning solution onto the base fabric obtained in step (1) by electrospinning to form a heat-storing gold film.
[0013] (4) After hot pressing the fabric obtained in step (3), the heat-insulating fabric based on the heat-storing gold film can be obtained.
[0014] As a further optimization of the present invention, in step (2), the ratio of sodium citrate to asiatic acid is 4-6:1.
[0015] As a further optimization of the present invention, in step (2), the mass ratio of nano-gold to sodium humate is 1:20-30.
[0016] As a further optimization of the present invention, in step (2), the process parameters of electrospinning are: pressure of 10-15kV, spinning solution injection speed of 0.1-0.5mm / min, collection speed of 50-60r / min, temperature of 25-30℃, and relative humidity of 30-40%.
[0017] As a further optimization of the present invention, in step (3), the hot pressing temperature is 150-160℃ and the time is 30-60s.
[0018] The beneficial effects of this invention are as follows:
[0019] The fabric of this invention is obtained by laminating a heat-retaining gold film onto a base fabric. The heat-retaining gold film is formed by first dispersing nano-gold in a polyurethane solution to obtain a spinning solution, and then electrospinning the spinning solution onto the base fabric. In the preparation of the nano-gold, firstly, the use of asiatic acid and sodium citrate makes the resulting nano-gold particles more uniform and dispersed, giving the fabric excellent breathability, moisture permeability, and heat retention, thus improving wearing comfort. Secondly, the addition of sodium humate enhances the fabric's antibacterial properties. Furthermore, after the nano-gold and sodium humate are mixed, they undergo friction treatment under vibration conditions, resulting in strong bonding between the nano-gold and sodium humate, preventing the nano-gold from agglomerating and ensuring the fabric has long-lasting heat retention and antibacterial effects. Detailed Implementation
[0020] The present application will now be described in further detail. It should be noted that the following specific embodiments are only used to further illustrate the present application and should not be construed as limiting the scope of protection of the present application. Those skilled in the art can make some non-essential improvements and adjustments to the present application based on the above application content.
[0021] Unless otherwise specified, all materials used in the following examples are commercially available.
[0022] Example 1
[0023] This embodiment provides a heat-insulating fabric based on a heat-storing gold film. The fabric structure includes a base fabric and a heat-storing gold film laminated on the base fabric. The base fabric is woven from 100% nylon fiber as warp yarn and 80% viscose fiber composite with 20% corn fiber hollow yarn as weft yarn by weight percentage. The heat-storing gold film is formed by first dispersing a nano-gold solution in a polyurethane solution to obtain a spinning solution, and then laminating the spinning solution onto the base fabric by electrospinning.
[0024] The preparation method of thermal insulation fabric based on heat-retaining gold film includes the following steps:
[0025] (1) Preparation of base fabric: By weight percentage, 100% 15D nylon fiber is made into warp yarn and 80% 15D viscose fiber is combined with 20% 20D corn fiber hollow yarn as weft yarn. The base fabric is obtained by weaving with a fabric weaving machine. The corn fiber hollow yarn is obtained by coating corn fiber with water-soluble polyvinyl alcohol fiber and then removing the water-soluble fiber by hydrolysis treatment (the hydrolysis treatment is a conventional water washing and soaking to remove the water-soluble polyvinyl alcohol fiber). The warp yarn weaving density is 90 threads / cm and the weft yarn weaving density is 70 threads / cm. The weave structure is plain weave.
[0026] (2) After filtering a 1% chloroauric acid aqueous solution through a 0.5 μm filter membrane, it was mixed with sodium citrate and asiatic acid (the mass ratio of sodium citrate to asiatic acid was 4:1). The total amount of sodium citrate and asiatic acid added was 5% of the volume of the chloroauric acid aqueous solution. The mixture was heated to boiling and kept for 2 hours to obtain a colloidal gold solution. The colloidal gold solution was then washed with ethanol and deionized water, centrifuged, and dried to obtain nano-gold. The nano-gold was mixed with sodium humate (mass ratio of 1:20) and rubbed at a speed of 100 r / min for 30 minutes under vibration.
[0027] (3) The nano-gold obtained in step (2) is dispersed in a polyurethane solution with a mass concentration of 15% to obtain a spinning solution. The amount of nano-gold is 5% of the mass of polyurethane. The spinning solution is spun onto the base fabric obtained in step (1) by electrospinning to form a heat-storing gold film. The electrospinning pressure is 10kV, the spinning solution injection speed is 0.1mm / min, the collection speed is 50r / min, the temperature is 25℃, and the relative humidity is 40%.
[0028] (4) After hot pressing the fabric obtained in step (3), the heat-insulating fabric based on the heat-storing gold film can be obtained. The hot pressing temperature is 150℃ and the time is 60s.
[0029] Example 2
[0030] This embodiment provides a heat-insulating fabric based on a heat-storing gold film. The fabric structure includes a base fabric and a heat-storing gold film laminated on the base fabric. The base fabric is woven from 100% nylon fiber as warp yarn and 60% viscose fiber composite with 40% corn fiber hollow yarn as weft yarn by weight percentage. The heat-storing gold film is formed by first dispersing a nano-gold solution in a polyurethane solution to obtain a spinning solution, and then electrospinning the spinning solution onto the base fabric.
[0031] The preparation method of thermal insulation fabric based on heat-retaining gold film includes the following steps:
[0032] (1) Preparation of base fabric: According to weight percentage, 100% 15D nylon fiber is made into warp yarn and 60% 15D viscose fiber is combined with 40% 20D corn fiber hollow yarn as weft yarn. The base fabric is obtained by weaving with a fabric weaving machine. The corn fiber hollow yarn is obtained by coating corn fiber with water-soluble polyvinyl alcohol fiber and then removing the water-soluble fiber by hydrolysis treatment. The warp yarn weaving density is 100 yarns / cm and the weft yarn weaving density is 80 yarns / cm. The weaving structure is plain weave.
[0033] (2) After filtering a 1% chloroauric acid aqueous solution through a 0.5 μm filter membrane, it was mixed with sodium citrate and asiatic acid (the mass ratio of sodium citrate to asiatic acid was 6:1). The total amount of sodium citrate and asiatic acid added was 5% of the volume of the chloroauric acid aqueous solution. The mixture was heated to boiling and kept for 2 hours to obtain a colloidal gold solution. The colloidal gold solution was then washed with ethanol and deionized water, centrifuged, and dried to obtain nano-gold. The nano-gold was mixed with sodium humate (mass ratio of 1:30) and rubbed at a speed of 80 r / min for 60 min under vibration.
[0034] (3) The nano-gold obtained in step (2) is dispersed in a polyurethane solution with a mass concentration of 15% to obtain a spinning solution. The amount of nano-gold is 5% of the mass of polyurethane. The spinning solution is spun onto the base fabric obtained in step (1) by electrospinning to form a heat-storing gold film. The electrospinning pressure is 10kV, the spinning solution injection speed is 0.1mm / min, the collection speed is 50r / min, the temperature is 25℃, and the relative humidity is 40%.
[0035] (4) After hot pressing the fabric obtained in step (3), the heat-insulating fabric based on the heat-storing gold film can be obtained. The hot pressing temperature is 150℃ and the time is 60s.
[0036] Example 3
[0037] This embodiment provides a heat-insulating fabric based on a heat-storing gold film. The fabric structure includes a base fabric and a heat-storing gold film laminated on the base fabric. The base fabric is woven from 100% nylon fiber as warp yarn and 80% viscose fiber composite with 20% corn fiber hollow yarn as weft yarn by weight percentage. The heat-storing gold film is formed by first dispersing a nano-gold solution in a polyurethane solution to obtain a spinning solution, and then laminating the spinning solution onto the base fabric by electrospinning.
[0038] The preparation method of thermal insulation fabric based on heat-retaining gold film includes the following steps:
[0039] (1) Same as Example 1;
[0040] (2) After filtering a 1% chloroauric acid aqueous solution through a 0.5 μm filter membrane, it was mixed with sodium citrate and asiatic acid (the mass ratio of sodium citrate to asiatic acid was 4:1). The total amount of sodium citrate and asiatic acid added was 5% of the volume of the chloroauric acid aqueous solution. The mixture was heated to boiling and kept for 2 hours to obtain a colloidal gold solution. The colloidal gold solution was then washed with ethanol and deionized water, centrifuged, and dried to obtain nano-gold. The nano-gold was mixed with sodium humate (mass ratio of 1:20) and rubbed at a speed of 100 r / min for 30 minutes under vibration.
[0041] (3) The nano-gold obtained in step (2) is dispersed in a polyurethane solution with a mass concentration of 15% to obtain a spinning solution. The amount of nano-gold is 5% of the mass of polyurethane. The spinning solution is spun onto the base fabric obtained in step (1) by electrospinning to form a heat-storing gold film. The electrospinning pressure is 10kV, the spinning solution injection speed is 0.1mm / min, the collection speed is 50r / min, the temperature is 25℃, and the relative humidity is 40%.
[0042] (4) After hot pressing the fabric obtained in step (3), the heat-insulating fabric based on the heat-storing gold film can be obtained. The hot pressing temperature is 150℃ and the time is 60s.
[0043] Verification test
[0044] 1. Investigate the influence of the base fabric structure on the fabric performance, and adjust the base fabric structure according to Table 1.
[0045] Table 1. Structural Composition of Base Fabric
[0046]
[0047] Note: The thickness of nylon fiber, viscose fiber, and corn fiber / corn fiber hollow yarn is selected in the same way as in Example 1.
[0048] Base fabrics 1-6 were prepared according to the preparation method of the base fabric disclosed in Example 1, and the following performance tests were performed on base fabrics 1-6:
[0049] (1) Tear resistance test: The test shall be conducted in accordance with GB / T3917-1:2009 "Tear resistance of fabrics - Part 1: Determination of tear strength by impact pendulum method".
[0050] (2) Air permeability test: Referring to the national standard (GB / T5433), the air permeability of the samples was tested using a YG461G type fully automatic fabric air permeability meter. The specific experimental parameters were set as follows: ambient temperature 25℃, relative humidity 60%, pressure difference 100Pa, and air permeability area 20cm². 2 The nozzle diameter is 0.8mm. Ten tests were conducted on different parts of the fabric sample, and the average value was taken as the final air permeability data.
[0051] (3) Moisture permeability test: According to national standard GB / T12704.1-2009(a), the moisture permeability of the samples was tested using an FX3180 moisture permeability meter. During the test, the temperature was 38℃, the humidity was 90.0%, the airflow velocity was 0.5m / s, and the test area was 28.3cm². 2Before testing, the test chamber needs to be pre-conditioned for humidity. After automatic humidity conditioning, the instrument begins the moisture permeability test, automatically recording moisture permeability data every hour for a total of two times. After the experiment is completed, the moisture permeability data of the samples are manually recorded, and the average of the five sets of experimental data for each sample is used as the final data.
[0052] The results are shown in Table 1.
[0053] Table 1. Fabric Performance Statistics
[0054]
[0055] As shown in Table 1, the tear resistance of base fabric 1 is inferior to that of base fabric 6. This is because the tear resistance of corn fiber hollow yarn is not as good as that of nylon fiber. However, in terms of air permeability, base fabric 5 is better than the other base fabrics because corn fiber has good air permeability. However, due to the generally low moisture permeability of corn fiber, the moisture permeability of base fabric 5 is lower than that of base fabrics 1-4, but still better than that of base fabric 6. In summary, the results in Table 1 indicate that base fabric 1, woven with 100% nylon fiber as warp and 80% viscose fiber combined with 20% corn fiber hollow yarn as weft, exhibits the best air and moisture permeability.
[0056] 2. To investigate the effect of the preparation method of the heat-storing gold film on the fabric performance, the following comparative examples were set up:
[0057] Comparative Example 1
[0058] This comparative example provides a method for preparing a thermal insulation fabric based on a heat-retaining gold film, including the following steps:
[0059] (1) The preparation of the base fabric is the same as in Example 1;
[0060] (2) After filtering a 1% chloroauric acid aqueous solution through a 0.5 μm filter membrane, it was mixed with sodium citrate and tannic acid (the mass ratio of sodium citrate to asiatic acid was 4:1). The total amount of sodium citrate and tannic acid added was 5% of the volume of the chloroauric acid aqueous solution. The mixture was heated to boiling and kept for 2 hours to obtain a colloidal gold solution. The colloidal gold solution was then washed with ethanol and deionized water, centrifuged, and dried to obtain nano-gold. The nano-gold was mixed with sodium humate (mass ratio of 1:20) and rubbed at a speed of 100 r / min for 30 minutes under vibration.
[0061] (3) The nano gold solution is dispersed in a polyurethane solution with a mass concentration of 15% to obtain a spinning solution. The amount of nano gold is 5% of the mass of polyurethane. The spinning solution is spun onto the base fabric obtained in step (1) by electrospinning to form a heat-storing gold film. The electrospinning pressure is 10kV, the spinning solution injection speed is 0.1-mm / min, the collection speed is 50r / min, the temperature is 25℃, and the relative humidity is 40%.
[0062] (4) Same as Example 1.
[0063] Comparative Example 2
[0064] This comparative example provides a method for preparing a thermal insulation fabric based on a heat-retaining gold film, including the following steps:
[0065] (1) The preparation of the base fabric is the same as in Example 1;
[0066] (2) After filtering a 1% chloroauric acid aqueous solution through a 0.5 μm filter membrane, it was mixed with sodium citrate and ascorbic acid (the mass ratio of sodium citrate to ascorbic acid was 4:1). The total amount of sodium citrate and ascorbic acid added was 5% of the volume of the chloroauric acid aqueous solution. The mixture was heated to boiling and kept for 2 hours to obtain a colloidal gold solution. The colloidal gold solution was then washed with ethanol and deionized water, centrifuged, and dried to obtain nano-gold. The nano-gold was mixed with sodium humate (mass ratio of 1:20) and rubbed at a speed of 100 r / min for 30 minutes under vibration.
[0067] (3) Same as Example 1;
[0068] (4) Same as Example 1.
[0069] Comparative Example 3
[0070] This comparative example provides a method for preparing a thermal insulation fabric based on a heat-retaining gold film, including the following steps:
[0071] (1) The preparation of the base fabric is the same as in Example 1;
[0072] (2) After filtering a 1% chloroauric acid aqueous solution through a 0.5 μm filter membrane, it was mixed with sodium citrate. The amount of sodium citrate added was 5% of the volume of the chloroauric acid aqueous solution. The mixture was heated to boiling and kept for 2 hours to obtain a colloidal gold solution. The colloidal gold solution was then washed with ethanol and deionized water, centrifuged, and dried to obtain nano-gold. The nano-gold was mixed with sodium humate (mass ratio of 1:20) and rubbed at a speed of 100 r / min for 30 minutes under vibration.
[0073] (3) Same as Example 1;
[0074] (4) Same as Example 1.
[0075] Comparative Example 4
[0076] This comparative example provides a method for preparing a thermal insulation fabric based on a heat-retaining gold film, including the following steps:
[0077] (1) The preparation of the base fabric is the same as in Example 1;
[0078] (2) A polyurethane solution with a mass concentration of 15% is spun onto the base fabric obtained in step (1) by electrospinning to form a heat-storing gold film. The electrospinning pressure is 10kV, the spinning solution injection speed is 0.1-mm / min, the collection speed is 50r / min, the temperature is 25℃, and the relative humidity is 40%.
[0079] (3) After hot pressing the fabric obtained in step (2), the heat-insulating fabric based on the heat-storing gold film can be obtained. The hot pressing temperature is 150℃ and the time is 60s.
[0080] Comparative Example 5
[0081] This comparative example provides a method for preparing a thermal insulation fabric based on a heat-retaining gold film, including the following steps:
[0082] (1) The preparation of the base fabric is the same as in Example 1;
[0083] (2) After filtering a 1% chloroauric acid aqueous solution through a 0.5 μm filter membrane, it was mixed with sodium citrate and asiatic acid (the mass ratio of sodium citrate to asiatic acid was 4:1). The total amount of sodium citrate and asiatic acid added was 5% of the volume of the chloroauric acid aqueous solution. The mixture was heated to boiling and kept for 2 hours to obtain a colloidal gold solution. The colloidal gold solution was then washed with ethanol and deionized water, centrifuged, and dried to obtain nano gold.
[0084] (3) Nano-gold and sodium humate were mixed (mass ratio 1:20) and dispersed in a 15% polyurethane solution to obtain a spinning solution. The amount of nano-gold was 5% of the mass of polyurethane. The spinning solution was spun onto the base fabric obtained in step (1) by electrospinning to form a heat-storing gold film. The electrospinning pressure was 10 kV, the spinning solution injection speed was 0.1 mm / min, the collection speed was 50 r / min, the temperature was 25℃, and the relative humidity was 40%.
[0085] (5) After hot pressing the fabric obtained in step (3), the heat-insulating fabric based on the heat-storing gold film can be obtained. The hot pressing temperature is 150℃ and the time is 60s.
[0086] Comparative Example 6
[0087] This comparative example provides a method for preparing a thermal insulation fabric based on a heat-retaining gold film, including the following steps:
[0088] (1) The preparation of the base fabric is the same as in Example 1;
[0089] (2) Same as Example 1;
[0090] (3) Nano gold and carbon powder (mass ratio of 1:20) were rubbed at a speed of 100 r / min for 30 min under vibration and then dispersed in a polyurethane solution with a mass concentration of 15% to obtain a spinning solution. The amount of nano gold was 5% of the mass of polyurethane. The spinning solution was spun onto the base fabric obtained in step (1) by electrospinning to form a heat-storing gold film. The electrospinning pressure was 10 kV, the spinning solution injection speed was 0.1 mm / min, the collection speed was 50 r / min, the temperature was 25℃, and the relative humidity was 40%.
[0091] (4) Same as Example 1.
[0092] First, the air permeability and moisture permeability of the fabrics prepared from base fabric 1, Example 1, and Comparative Examples 1-6 were tested:
[0093] (1) Air permeability test: Referring to the national standard (GB / T5433), the air permeability of the samples was tested using a YG461G type fully automatic fabric air permeability meter. The specific experimental parameters were set as follows: ambient temperature 25℃, relative humidity 60%, pressure difference 100Pa, and air permeability area 20cm². 2 The nozzle diameter is 0.8mm. Ten tests were conducted on different parts of the fabric sample, and the average value was taken as the final air permeability data.
[0094] (2) Moisture permeability test: According to national standard GB / T12704.1-2009(a), the moisture permeability of the samples was tested using an FX3180 moisture permeability measuring instrument. During the test, the temperature was 38℃, the humidity was 90.0%, the airflow velocity was 0.5m / s, and the test area was 28.3cm². 2 Before testing, the test chamber needs to be pre-conditioned for humidity. After automatic humidity conditioning, the instrument begins the moisture permeability test, automatically recording moisture permeability data every hour for a total of two times. After the experiment is completed, the moisture permeability data of the samples are manually recorded, and the average of the five sets of experimental data for each sample is used as the final data.
[0095] Table 2. Statistical Table of Fabric Breathability and Moisture Permeability
[0096]
[0097] As can be seen from Table 2, comparing Example 1 with base fabric 1, it can be seen that the air permeability and moisture permeability of the fabric are reduced to a certain extent due to the coating. Compared with Example 1, the air permeability and moisture permeability of the fabrics in Comparative Examples 1-2 are not as good. In the preparation of nano-gold, Comparative Examples 1-2 used tannic acid and ascorbic acid instead of asiatic acid, respectively. The results show that asiatic acid, compared with tannic acid and ascorbic acid, is more effective in promoting the formation of more uniform and dispersed nano-gold particles and more uniform distribution of micropores on the membrane, thus improving the air permeability and moisture permeability of the fabric.
[0098] Compared to Example 1, Comparative Example 5 differs in that the nano-gold and sodium humate mixture was not subjected to friction treatment under vibration. The results show that adding the friction step under vibration can promote the dispersion of nano-gold in the polyurethane solution, making it less prone to agglomeration. The uniform micropore distribution on the film improves the breathability and moisture permeability of the fabric.
[0099] Subsequently, the thermal insulation performance of the fabrics prepared by base fabric 1, Example 1 and Comparative Examples 1-6 was tested: Eight glass bottles containing water at 90°C were wrapped with double-layer thermal insulation fabrics prepared by base fabric 1, Example 1 and Comparative Examples 1-5 respectively, and then placed in a normal temperature environment. The temperature change of the thermometer was observed and the water temperature in the glass bottle was recorded after 5 hours. The temperature loss rate was calculated and the results are shown in Table 3.
[0100] Table 2. Statistical Table of Fabric Thermal Insulation Performance
[0101]
[0102]
[0103] As can be seen from Table 3, the fabric prepared in Example 1 has better heat retention performance than other groups after 0 and 50 washes. Compared with Example 1, Comparative Examples 1-2 used tannic acid and ascorbic acid instead of asiatic acid when preparing nano-gold, respectively. The fabrics prepared in Comparative Examples 1-2 had worse heat retention performance after 0 and 50 washes than Example 1. The reason is that when preparing colloidal gold, the combination of asiatic acid and sodium citrate makes the nano-gold particles more uniform and dispersed. The nano-gold is easier to disperse in polyurethane solution, and the heat-storing gold film has good uniformity, which can better exert the heat retention effect.
[0104] Compared to Example 1, Comparative Example 5 differs in that the nano-gold and sodium humate were not subjected to friction treatment under vibration. The resulting fabric had lower heat retention performance after 0 and 50 washes than that of Example 1. This is because the bonding force between the nano-gold and sodium humate was weaker without vibration friction treatment, and the nano-gold was more prone to agglomeration, resulting in poor uniformity of the heat-storing gold film and reduced heat retention performance of the fabric.
[0105] Compared to Example 1, Comparative Example 6 did not add sodium humate. The fabric's heat retention performance after 0 and 50 washes was not as good as that of Example 1. It can be seen that the addition of sodium humate has a positive effect on improving the heat retention performance of the fabric.
[0106] Finally, the antibacterial properties of the fabrics prepared from base fabric 1, Example 1, and Comparative Examples 1-6 were tested. The antibacterial test method was based on GB / T20944.2-2007 "Evaluation of Antibacterial Properties of Textiles" Part 2: Absorption Method. The test bacteria were Staphylococcus aureus ATCC No. 6538 (Gram-positive bacteria) and Escherichia coli 8099 (Gram-negative bacteria). The fabrics from Example 1 and Comparative Examples 1-6 were cut into 20mm × 20mm pieces and subjected to antibacterial tests after 0 and 50 washes, respectively. The results are shown in Table 4.
[0107] Table 4. Antibacterial test results
[0108]
[0109]
[0110] As shown in Table 3, the fabric prepared in Example 1 exhibited the best antibacterial properties, with no significant difference compared to Comparative Examples 1-2. This indicates that replacing asiatic acid with tannic acid and ascorbic acid during the preparation of nano-gold does not significantly reduce the fabric's antibacterial properties. Comparing Example 1 with Comparative Example 5, the antibacterial properties of the fabric in Comparative Example 5 after 0 washes were comparable to those in Example 1. However, after 50 washes, the antibacterial properties of the fabric in Comparative Example 5 significantly decreased compared to Example 1. The difference between Example 1 and Comparative Example 5 lies in the fact that, during the preparation of the heat-storing gold film, the nano-gold and sodium humate were not subjected to friction treatment under vibration conditions after mixing. This resulted in a weaker binding force between the nano-gold and sodium humate, leading to a decrease in antibacterial properties after multiple washes. Comparative Example 6 showed lower antibacterial properties than Example 1 because it used carbon powder instead of sodium humate in Example 1. This demonstrates that sodium humate has a positive impact on improving the fabric's antibacterial properties.
[0111] The embodiments described above are merely examples of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the present invention. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these modifications and improvements all fall within the scope of protection of the present invention.
Claims
1. A thermal insulation fabric based on a heat-retaining gold film, characterized in that: The fabric structure includes a base fabric and a heat-retaining gold film laminated on the base fabric; wherein, the base fabric is woven from 100% nylon fiber as warp yarn and 60-80% viscose fiber composite with 20-40% corn fiber hollow yarn as weft yarn by weight percentage; the heat-retaining gold film is formed by first dispersing nano-gold in a polyurethane solution to obtain a spinning solution, and then laminating the spinning solution onto the base fabric by electrospinning; The method for preparing the heat-insulating fabric based on the heat-retaining gold film includes the following steps: (1) Preparation of base fabric: The base fabric is obtained by weaving nylon fiber as warp yarn and viscose fiber composite corn fiber hollow yarn as weft yarn using a fabric weaving machine; (2) After filtering the aqueous solution of chloroauric acid through a 0.5 μm filter membrane, it is mixed with sodium citrate and asiatic acid, heated to boiling, and kept for 1-5 h to obtain a colloidal gold solution. Then, the colloidal gold solution is washed with ethanol and deionized water, centrifuged, and dried to obtain nano gold. The nano gold is mixed with sodium humate and rubbed at a speed of 80-100 r / min for 30-60 min under vibration. (3) The nano gold obtained in step (2) is dispersed in a polyurethane solution to obtain a spinning solution, and the spinning solution is spun onto the base fabric obtained in step (1) by electrospinning to form a heat-storing gold film. (4) After hot pressing the fabric obtained in step (3), the heat-insulating fabric based on the heat-storing gold film can be obtained.
2. The thermal insulation fabric based on a heat-retaining gold film according to claim 1, characterized in that: The warp yarn density is 90-100 yarns / cm, the weft yarn density is 70-80 yarns / cm, and the weave structure is plain weave.
3. The thermal insulation fabric based on a heat-retaining gold film according to claim 1, characterized in that: The corn fiber hollow yarn is obtained by coating corn fiber with water-soluble fiber and then removing the water-soluble fiber through hydrolysis. The water-soluble fiber is water-soluble polyvinyl alcohol fiber.
4. The thermal insulation fabric based on a heat-retaining gold film according to claim 1, characterized in that: In step (2), the mass ratio of sodium citrate to asiatic acid is 4-6:
1.
5. The thermal insulation fabric based on a heat-retaining gold film according to claim 1, characterized in that: In step (2), the mass ratio of nano-gold to sodium humate is 1:20-30.
6. The thermal insulation fabric based on a heat-retaining gold film according to claim 1, characterized in that: In step (3), the electrospinning process parameters are: pressure of 10-15kV, spinning solution injection speed of 0.1-0.5mm / min, collection speed of 50-60r / min, temperature of 25-30℃, and relative humidity of 30-40%.
7. The thermal insulation fabric based on a heat-retaining gold film according to claim 1, characterized in that: In step (4), the hot pressing temperature is 150-160℃ and the time is 30-60s.
Citation Information
Patent Citations
Anti-radiation odor-resistant fabric
CN105369606A
Antibacterial waterproof moisture-permeable nano fiber membrane and preparation method thereof
CN107829213A